The Effect of Health Education on Elderly Women Life Quality - S Mohamadlo; F Bahadori; F Broomand; M Hajshafiha; A Amirai; H Mohaddesi; F Nanbakhsh (Tehran University of Medical Sciences, 2011)
Background and Aim: Elderly is a physiological phenomenon with many inevitable complications, which their effects significantly can be reduced by individual's life style. Therefore in this study we have evaluated the impact of subjects' knowledge on their lifestyle.Materials and Methods: This study was a semi experimental and interventional one that has been conducted in Urmia University of Medical Science. Thus 200 women between 54 to 80 years old were enrolled in this study and their knowledge, attitude and behavior toward a healthy lifestyle was surveyed before and 6 months after giving them a proper education. Subsequently the required information gathered from questionnaires and the data analyzed by mcmanaman paired and t paired tests. In this study all data analyzed by SPSS software and the P value lessu than 0.05 recognized to be statistically significant.Results: The scores of before and 6 months after subjects get the required education were 29.165.86 vs. 34.266.32 respectively (P<0.001). This significant difference demonstrates the positive impact of life style education on attitude, behavior and knowledge of individuals in respect to their lifestyle. These results were even more magnificent comparing the literate and illiterate subjects.Conclusion: Based on our study we conclude that education has an important positive role in all elder groups improving their lifestyle.